PENGARUH PENGGUNAAN MINYAK BIJI KARET EPOKSI DAN BAHAN PENGISI PENGUAT TERHADAP KARAKTERISTIK KOMPON KARET - Popy Marlina (Balai Riset dan Standardisasi Industri Palembang, 2010)
The research aimed to know the effects of epoxide rubber seed oil and reinforcing filler on characteristics of rubber compound. Reinforcing filler type used carbon black and silica. The experiment was designed into three formulas, such as Formula I (exposide rubber seed oil 5 phr and without filler), Formula II (epoxide rubber seed oil 5 phr and carbon black 40 phr), Formula III (rubber seed oil 5 phr and silica 40 phr). The result show that the addition of exposide rubber seed oil, carbon black and silica had significant effect on the hardness, tensile strength, modulus 300% and abration resistence, The best treatment was found to be the Formula II (epoxide rubber seed oil 5 phr and carbon black 40 phr) with the rubber compound’s charasteristics of 70 shore A for hardness, 250,5 kg/cm2 for tensile strength, 102 kg/cm2 for modulus 300% and 128,7 kg/cm2 for abration resistence.